2018
DOI: 10.21608/edj.2018.76370
|View full text |Cite
|
Sign up to set email alerts
|

The effect of saliva and blood contamination on the bond characteristics of metal bracket bonded by light cured cyanoacrylate adhesive

Abstract: Purpose: This study was aimed to evaluate the effect of saliva and blood contamination on shear bond strength of metal brackets bonded with light cured cyanoacrylate adhesive. Material and methods: The study was conducted on 75 extracted upper first premolars. Metal orthodontic brackets were bonded to the buccal surfaces of the premolars using Smart bond LC adhesive. The teeth were divided into 5 equal groups. In group I no the teeth were not subjected to contamination. In Group II and III the same procedures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
1
0
3
Order By: Relevance
“…They concluded that premedication for saliva reduction did not affect the SBS. Hafez and Nassar [ 22 ] studied the effect of blood and saliva contamination on SBS of metal brackets bonded with light-cure cyanoacrylate adhesive. They found that blood contamination of the enamel surface significantly decreased the SBS.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that premedication for saliva reduction did not affect the SBS. Hafez and Nassar [ 22 ] studied the effect of blood and saliva contamination on SBS of metal brackets bonded with light-cure cyanoacrylate adhesive. They found that blood contamination of the enamel surface significantly decreased the SBS.…”
Section: Discussionmentioning
confidence: 99%
“…De acordo com Hafez & Nassar (2018) que também avaliaram a resistência ao cisalhamento de bráquetes metálicos, colados com adesivo de cianocrilato fotopolimerizavel, diante da contaminação do de saliva e sangue, dividindo-se em: grupo I, feito o condicionamento com ácido fosfórico 37%, manteve-se o elemento molhado e foi aplicada uma fina camada de Smartbond LC; nos grupos II e III seguindo o mesmo protocolo, o esmalte foi contaminado com saliva e sangue respectivamente; nos grupos IV e V foram contaminados com saliva e sangue respectivamente, e em seguida lavados com água. Os resultados revelaram significativas diferenças na força de ligação entre os diferentes grupos e os diferentes protocolos de contaminação.…”
Section: De Acordo Com Lon Et Al (2018) Observaram a Resistência Ao Cisalhamento De Braquetes Ortodônticos Colados Comunclassified
“…Então, SmartBond LC tem resistência ao cisalhamento aceitável, e a contaminação saliva não causou nenhum efeito danoso sobre a resistência de união, enquanto que a contaminação por sangue proporcionou um efeito deletério sobre a Research, Society and Development, v. 10, n. 6, e58910616012, 2021 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v10i6.16012 resistência de união, no entanto, a lavagem com água pode reduzir esse efeito. O adesivo tanto em meio seco, como úmido proporcionou um padrão de fratura adesiva (Hafez & Nassar, 2018). Vicente et al, (2010) avaliaram a resistência ao cisalhamento e o local de falha dos bráquetes colados ao esmalte em meio úmido e seco.…”
Section: De Acordo Com Lon Et Al (2018) Observaram a Resistência Ao Cisalhamento De Braquetes Ortodônticos Colados Comunclassified
See 1 more Smart Citation